2008
DOI: 10.1038/oby.2007.88
|View full text |Cite
|
Sign up to set email alerts
|

Headaches in Overweight Children and Adolescents Referred to a Tertiary‐care Center in Israel

Abstract: objective: To assess the association between obesity and primary headaches in children and adolescents. Methods and Procedures: In a prospective study, the short-questionnaire version based on existing International Headache Society diagnostic criteria was administered. Two hundred and seventy-three children and adolescents (61% females) aged 9-17 years were assessed. One hundred and sixteen (42.5%) subjects were of normal weight, 45 (16.5%) were at risk for overweight (BMI >85th and <95th percentile for age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 24 publications
7
73
3
2
Order By: Relevance
“…Data regarding effects of obesity and headaches in children are more limited. However, an increasing number of reports suggest that obesity could also be a risk factor for migraine in the paediatric population [38][39][40]. Our study confirmed these findings.…”
Section: Discussionsupporting
confidence: 83%
“…Data regarding effects of obesity and headaches in children are more limited. However, an increasing number of reports suggest that obesity could also be a risk factor for migraine in the paediatric population [38][39][40]. Our study confirmed these findings.…”
Section: Discussionsupporting
confidence: 83%
“…Comorbidity with obesity has been reported in children and in adults with headaches (3,(23)(24)(25), but both of these conditions are widespread and conclusive results are difficult to obtain. In obese …”
Section: Discussionmentioning
confidence: 99%
“…Other associated conditions are epilepsy (10-15), asthma and allergic disorders (16), sleep disorders (17-21), celiac disease (CD) (22), and obesity (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…20,65 Overweight females had a near four fold excess risk of headache when compared to normal-weight girls; there was no relationship between weight and headache in males. 66 …”
Section: Obesitymentioning
confidence: 99%